Beyond the positivism in the philosophy of interlational law: Bianchi and the ludic approach of interpretation - Rosales Zamora, Pablo César (2022)
The present paper has as aim exploring the scientific consideration of international law from the positivism, to hold the postmodern position that emphasizes the importance of interpretative role is the more adequate to explain the jurisdictional phenomenon of contemporary international law, above all by the presence of multiple permanent international tribunals. For this research, it has considered Kelsen and Bianchi as representative of both epistemological approaches, respectively. In this sense, the article examines the Bianchi´s approach on interpretation, which considers interpretation as a ludic activity to own an objective, a specific context, rules, players and strategies.